The kinetics of update and release of polycyclic aromatic hydrocarbons in the green mussels perna viridis for biomonitoring of marine pollution - Moradi, Ali Mashinchian (2001)
The kinetics of accumulation and depuration of polycyclic aromatic hydrocarbons (PAHs) in green mussel Perna viridis has never been investigated under field conditions. In this study, green mussels were used to assess the spatial distribution of PAH pollution along the west coast of Peninsular Malaysia, and to determine PAHs uptake and release kinetics in this species under field conditions. In addition, the effect of sex and exposure duration on the uptake and release kinetics of these contaminants were investigated. Overall more than 1500 individual mussels were collected, soft tissues were homogenized, extracted, cleaned up, fractionated and concentration of 17 individual PAH compounds were analysed using Gas Chromatography-Mass Spectrometry (GC-MS). Among the eleven stations sampled in 1997 and 1998 along the Straits of Malacca, mussels from Pasir Puteh (01˚ 26.05' N and 103˚ 55.94' E) had the highest (2855-3450 nglg lipid weight) and from Pasir Panjang (02˚ 24.96' N and 101˚ 56.54' E) the lowest (278-366 ng/g lipid weight) levels of PAHs. As a result, Pasir Puteh was selected as the "hot-spot" and Pasir Panjang as the "clean site" to further conduct the kinetics experiments. The PAH levels in mussels from Malaysian coastlines in comparison with the polluted areas worldwide were found to be relatively low. At the end of both uptake and release experiments (28 and 36 days, respectively), PAH levels in transplanted and back transplanted mussels were not significantly different (p>0.05) from those found in natives (controls in Pasir Puteh and Pasir Panjang, respectively). It was found that sex did not make a significant difference (p>0.05) in the uptake and release rates. Similarly, duration of exposure did not significantly affect the release rates. However, significant differences (p<0.05) were found both in uptake and release rates when target PAHs were divided into three, four and five to seven-ring compounds. In general, rapid rates of uptake and release of relatively less lipophilic PAHs were observed, indicating that the primary mechanism of bioaccumulation of these lipophilic pollutants in Perna viridis complies with the concept of lipid-water partitioning equilibrium. The biological half-life of individual PAHs ranged from 7 to 29 days. This study illustrated that green mussels are a useful tool in monitoring of PAHs. However, due to relatively rapid rates of uptake and release of these compounds, to get an average level of PAHs over a long period, "time-bulking" should be considered for future biomonitoring programmes using this species.